Moral distance and moral motivations in dictator games - Fernando Aguiar; Pablo Bra\~nas-Garza; Luis M. Miller (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We perform an experimenta linvestigation using a dictator game in which individuals must make a moral decision to give or not to give an amount of money to poor people in the Third World. A questionnaire in which the subjects are asked about the reasons for their decision shows that, at least in this case, moral motivations carry a heavy weight in the decision: the majority of dictators give the money for reasons of a consequentialist nature. Based on the results presented here and of other analogous experiments, we conclude that dicator behavior can be understood in terms of moral distance rather than social distance and that it systematically deviates from the egoism assumption in economic models and game theory.
Keywords: A13; C72; C91; 330; Dictator game; moral distance; moral motivations; experimental economics; Verhandlungstheorie; Nichtkooperatives Spiel; Spende; Private Entwicklungshilfe; Entscheidung; Ethik; Test